COMPUTATIONAL INVESTIGATION OF UNGLAZED SELECTIVE COLLECTOR AND SINGLE ONE WITH PLEXIGLAS AS COVER BASED ON EXERGETIC PERFORMANCE CRITERIA - Kaze C.V., Aloyem; Rene, Tchinda (European Scientific Journal, ESJ, 2014)
In this paper, performance assessment of two solar air systems isconducted through energy and exergy analysis. One is an unglazed selectiveabsorber (C1) and the second is a single one solar air with the polymethylmethacrylate as cover (C2). The mean hourly values of solar irradiation andambient temperature of Garoua region in Cameroon are used. The influenceof the solar air heater duct depth and the number of transfer units on theexergy output is discussed. The main results we can draw are that at 12:30,the exergy output rate (Exu) of the first collector is almost five times the oneof the second collector. The highest dimensionless exergy loss occurred inthe collector with plastic cover while the lowest through unglazed collector.It has been also observed that for NTU (Number of Transfer Units) higherthan 1.8, the exergy output rate increases weakly and becomes constant forNTU greater than 2.5.